ARGUMENTASI HUKUM OLEH HAKIM DALAM MENILAI BUKTI HUKUM YANG DIAJUKAN PENGGUGAT - Pratama, Aldita Putra Bayu; Suseno, Irit; Prasetyawati, Endang (Jurnal Hukum Magnum Opus, 2021)
AbstractThis scientific work aims to find out how the legal arguments for the judge's decision in the legal evidence submitted by the plaintiff during the evidentiary process at trial. And to find out the implementation process, this work uses a normative method, namely researching and analyzing legal materials in the form of secondary legal materials by understanding a law as a positive rule or norm in a statutory system that regulates human daily life in behavior. Sources of legal materials are obtained from literature, laws and regulations as well as opinions from legal experts. The analysis used goes through several stages, legal materials related to the formulation of the problem being discussed, then analyzed by steps, legal interpretation, systematization, evaluation, and legal argumentation. Article 5 paragraph (1) of the Law on Judicial Power explains: judges need to be obliged to examine, understand, follow the values of law and the sense of justice that exists in society. For this reason, in the process of evidence in court, the judge must really assess the evidence presented by the plaintiff and consider it in the verdict. In the research results, it was concluded that in the process of legal argumentation by judges, it must be carried out fairly and fairly and not biased so as not to harm either party between the plaintiffs or the defendants. Because after all the decisions issued by judges are also one of the sources of law in civil procedural law. With judges looking at Article 5 atat 1 of the Law on Judicial Power to assess legal evidence in court, it is hoped that it can improve the performance of judges in upholding the law in Indonesia.Keywords: evidence; judge's considerationAbstrakKarya ilmiah ini memiliki tujuan untuk mencari tahu gimana argumentasi hukum putusan hakim dalam bukti hukum yang diajukan penggugat pada saat proses pembuktian di persidangan. Dan untuk mengetahui proses pelaksanaannya, dalam karya ini menggunakan methode normatip yaitu meneliti serta menganalisis bahan hukum yang berupa beberapa bahan hukum sekunder dengan cara memahami suatu hukum sebagai peraturan atau norma positip dalam sistim perundang-undangan yang mengatur tentang kehidupan sehari-hari manusia dalam berperilaku. Sumber bahan hukum diperoleh dari literatur, peraturan perundangan dan juga pendapat dari para pakar dibidang hukum. Analisis yang dipakai menggunakan melalui beberapa tahapan, bahan-bahan hukum terkait  rumusan masalah yang sedang dibahas, selanjutnya dianalisis dengan langkah, interpretasi hukum, sistematisasi, evaluasi, serta argumentasi hukum. Pasal 5 ayat (1) UU Kekuasaan Kehakiman menjelaskan  hakim perlu wajib menelaah, memahami, mengikuti nilai-nilai hukum dan rasa keadilan yang hidup/ada pada masyarakat. Untuk itu dalam proses pembuktian di persidangan hakim harus benar-benar menilai bukti yang diajukan penggugat serta mempertimbangkan dalam amar putusannya. Dalam hasil penelitian disimpulkan bahwa dalam proses argumentasi hukum oleh hakim haruslah dilakukan secara seadil-adilnya dan tidak berat sebelah agar tidak merugikan salah satu pihak antar penggugat maupun terggugat. Karena bagaimanapun juga putusan yang dikeluarkan hakim juga merupakan salah satu sumber hukum dari hukum acara perdata. Dengan hakim melihat pada Pasal 5 ayat (1) UU Kekuasaan Kehakiman untuk menilai bukti hukum di persidangan diharapkan dapat memperbaiki kinerja hakim dalam menegakan hukum di Indonesia.